DESCRIPTIVE STUDY OF THE COMPETENCE OF SPECIAL GUIDANCE TEACHERS FOR INCLUSIVE SCHOOLS IN SURAKARTA - Arifin, Misbahul; Yusuf, Munawir; Yuwono, Joko (Transpublika Publisher, 2021)
Inclusive education is education that allows learners with mental or physical disabilities the equal opportunity to learn alongside peers their age in regular schools. Inclusive education tries to minimize negative perceptions toward children with disabilities. A special guidance teacher's role is significant in maximizing children's academic and non-academic development. The purpose of this study is to determine how to optimize the role and responsibilities of special guidance teachers in inclusion schools, to ascertain the impact that the absence of special guidance teachers has on inclusion schools, and to ascertain the school's efforts to overcome the effects of the unavailability of special guidance teachers in inclusion schools. The descriptive qualitative method was used in this study. The study gathered data from principals, special guidance teachers, and classroom teachers. Interviews, observations, documentation, and questionnaires are used to collect data. The findings of this study indicate that special guidance teachers (GPK) continue to exercise authority in the same way that other teachers do, namely by standing in the classroom and instructing children with special needs. Special guidance teachers educate in the same way as classroom teachers, and some even shift to classroom teaching as a result of the school's teacher shortage. The impact on schools caused by the lack of special guidance teachers in inclusion education is the inability to meet the needs of ABK (children with special needs), especially special needs programs; ABK (children with special needs) is seen as a disruptor in the smooth implementation of educational programs; classroom teachers are unable to accommodate the needs of ABK in the classroom; school policy to accept both regular students and ABK (children with special needs) with mild level disabilities. While ABK with a moderate to severe level of resistance is directed at Special Needs Schools (SLB). To address the lack of GPK, efforts are undertaken to appoint honoree GPK and to collaborate with the nearest SLB to bring in visiting teachers. Keywords: Special Guidance Teachers, Inclusive Schools, Children with Special Needs